2020
DOI: 10.3389/fonc.2020.605737
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Four-Gene Signature Associated With Immune Checkpoint for Predicting Prognosis in Lower-Grade Glioma

Abstract: The overall survival of patients with lower grade glioma (LGG) varies greatly, but the current histopathological classification has limitations in predicting patients’ prognosis. Therefore, this study aims to find potential therapeutic target genes and establish a gene signature for predicting the prognosis of LGG. CD44 is a marker of tumor stem cells and has prognostic value in various tumors, but its role in LGG is unclear. By analyzing three glioma datasets from Gene Expression Omnibus (GEO) database, CD44 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 96 publications
0
11
0
Order By: Relevance
“…The classification combined molecular characteristics and histology, which then categorized grade II and grade III gliomas as well as grade IV glioblastomas (GBMs) as diffuse gliomas [1]. Because of convergence of many features of the grade II and grade III gliomas, they are collectively referred to as lower grade gliomas (LGGs) [2].…”
Section: Introductionmentioning
confidence: 99%
“…The classification combined molecular characteristics and histology, which then categorized grade II and grade III gliomas as well as grade IV glioblastomas (GBMs) as diffuse gliomas [1]. Because of convergence of many features of the grade II and grade III gliomas, they are collectively referred to as lower grade gliomas (LGGs) [2].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the expression of IFNG gene signature (including IDO1, CXCL10, CXCL9, HLA-DRA, STAT1, and IFNG), as well as expanded IFNG gene signature (including 18 genes involved in the IFNG response and major downstream pathways), characterizes the T-cell inflamed phenotype well, acts as an effective indicator for screen potential responders to ICB therapy, and is a marker of improved prognosis for most tumors, except for gliomas ( Danaher et al, 2018 ; Qian et al, 2018 ). Besides, another four-gene signature associated with immune pathways and the expression of immune checkpoints also predicts a poor prognosis for patients with lower-grade glioma ( Xiao et al, 2020 ). These results may suggest that excessive immune responses do not benefit glioma patients, even if more tumor cells can be eliminated, in line with our IRG-based gene signature to characterize immune activation while being associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, prognostic factors (IDH status, WHO Grade, 1p/19q co-deletion) have been found to correlate with immune checkpoint expression. Xiao et al suggested that higher immune checkpoint expression in the high-risk group of LGG patients with the same IDH status may be associated with activation of immunosuppressive pathways (30). In a study by Lei Lv et al, it was noted that 1p/ 19q co-deletion could lead to reduced expression levels of several immune checkpoints, including PD1 and PD-L1/2, and suggested that both IDH mutations and 1p/19q co-deletion are markers of better prognosis in LGG patients (31).…”
Section: Discussionmentioning
confidence: 99%